2017
DOI: 10.1038/srep46637
|View full text |Cite
|
Sign up to set email alerts
|

Bio-inspired, large scale, highly-scattering films for nanoparticle-alternative white surfaces

Abstract: Inspired by the white beetle of the genus Cyphochilus, we fabricate ultra-thin, porous PMMA films by foaming with CO2 saturation. Optimising pore diameter and fraction in terms of broad-band reflectance results in very thin films with exceptional whiteness. Already films with 60 µm-thick scattering layer feature a whiteness with a reflectance of 90%. Even 9 µm thin scattering layers appear white with a reflectance above 57%. The transport mean free path in the artificial films is between 3.5 µm and 4 µm being … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
69
0

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 60 publications
(70 citation statements)
references
References 53 publications
0
69
0
Order By: Relevance
“…However, the widespread use of TiO 2 particles as scattering enhancers, for example in food, cosmetics, and paper, has recently raised serious health and environmental concerns . Therefore, there is a real need to improve scattering efficiency using more sustainable and biocompatible materials …”
mentioning
confidence: 99%
“…However, the widespread use of TiO 2 particles as scattering enhancers, for example in food, cosmetics, and paper, has recently raised serious health and environmental concerns . Therefore, there is a real need to improve scattering efficiency using more sustainable and biocompatible materials …”
mentioning
confidence: 99%
“…The structural coloration inspired by the wings of butterflies and beetles boasts optical properties such as iridescence, polarization caused by interference, scattering, and diffraction. In Figure , biologically inspired structures for structural coloration are anatomically categorized, depending on approach and process design from a single‐layer level, a multilayer level, a sculpture level, to a quasi‐ordered level . Textures on the layer itself, for example, holes, C‐grooves, and zigzags in Figure a, produce structural colors.…”
Section: Insect‐inspired Structural Colors For Imaging and Displaymentioning
confidence: 99%
“…Wings as well as eyes of a butterfly serve as a distinctive structural color template, arisen from natural photonic crystals with multistacked layers . Advanced from biological structural coloration, a transparent long‐pass filter inspired by Morpho butterfly is nanofabricated by self‐assembly and ultrathin, porous methyl methacrylate (PMMA) films, inspired by the white beetle of Cyphochilus insulanus , provide consistent whiteness. Besides, various micro/nanostructures found in fireflies, moth eye, and compound eye make use of highly efficient light extraction to directly suit modern lighting technologies such as a light‐emitting diode (LED) and an organic light‐emitting diode (OLED).…”
Section: Introductionmentioning
confidence: 99%
“…While it has been recently found that certain white butterflies try to compensate for the low refractive index of chitin exploiting the dispersion induced by a high concentration of UV‐absorbing pigments, the exceptional bright whiteness of the Cyphochilus beetle stems exclusively from its optimized network structure, which has raised a lot of interest in different fields as it proves that highly efficient scattering materials can be obtained from more readily available low refractive index materials such as polymers. Furthermore, its network structure holds promise for the development of particle‐free scattering media, which are being actively sought after in recent years due to health‐ and environment‐related concerns about nanoparticle‐based scattering media …”
Section: Introductionmentioning
confidence: 99%
“…To date, methods such as electrospinning, supercritical carbon dioxide foaming (SC‐CO 2 ), and cellulose nanocrystal (CNC) self‐assembly have been proposed to prepare bright‐white surfaces using polymers with low refractive index, but have failed to match the optical performance of the Cyphochilus beetles. More recently, poly(methyl methacrylate) (PMMA) films prepared by a nonsolvent‐induced polymer phase separation (NIPS) method, where the phase separation of the polymer is caused by adding the nonsolvent into the polymer solution before solvent evaporation, have been reported exhibiting a scattering strength comparable to that of the beetle .…”
Section: Introductionmentioning
confidence: 99%